The protein kinase PKR is required for p38 MAPK activation and the innate immune response to bacterial endotoxin - Goh, Kee Chuan; deVeer, Michael J.; Williams, Bryan R.G. (The EMBO journal, 2000)
Protein kinase RNA‐regulated (PKR) is an established component of innate antiviral immunity. Recently, PKR has been shown to be essential for signal transduction in other situations of cellular stress. The relationship between PKR and the stress‐activated protein kinases (SAPKs), such as p38 mitogen‐activated protein kinase (MAPK), is not clear. Using embryonic fibroblasts from PKR wild‐type and null mice, we established a requirement for PKR in the activation of SAPKs by double‐stranded RNA, lipopolysaccharide (LPS) and proinflammatory cytokines. This does not reflect a global failure to activate SAPKs in the PKR‐null background as these kinases are activated normally by anisomycin and other physicochemical stress. Activation of p38 MAPK was restored in immortalized PKR‐null cells by reconstitution with human PKR. We also show that LPS induction of interleukin‐6 and interleukin‐12 mRNA is defective in PKR‐null cells, and that production of these cytokines is impaired in PKR‐null mice challenged with LPS. Our findings indicate, for the first time, that PKR is required for p38 MAPK signaling and plays a potentially important role in the innate response against bacterial endotoxin.